2008
DOI: 10.1128/aem.01233-08
|View full text |Cite
|
Sign up to set email alerts
|

Time-Lapse Microscopy of Streptomyces coelicolor Growth and Sporulation

Abstract: Bacteria from the genus Streptomyces are among the most complex of all prokaryotes; not only do they grow as a complex mycelium, they also differentiate to form aerial hyphae before developing further to form spore chains. This developmental heterogeneity of streptomycete microcolonies makes studying the dynamic processes that contribute to growth and development a challenging procedure. As a result, in order to study the mechanisms that underpin streptomycete growth, we have developed a system for studying hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 32 publications
(28 reference statements)
2
36
0
Order By: Relevance
“…Wonderful movies of septum formation during early growth of the hyphae of S. coelicolor show how irregular the placement of septa is in vegetative hyphae, with cross-walls dividing the vegetative hyphae into multigenomic compartments (276). In contrast, during sporulation-specific cell division in aerial hyphae, many septa are formed almost simultaneously and in a highly symmetrical fashion, followed by the formation of spore compartments and cell fission, resulting in chains of spores that each contain a single copy of the chromosome (reviewed in references 277 and 278).…”
Section: From Aerial Hyphae To Spores: Sporulation-specific Cell Divimentioning
confidence: 99%
“…Wonderful movies of septum formation during early growth of the hyphae of S. coelicolor show how irregular the placement of septa is in vegetative hyphae, with cross-walls dividing the vegetative hyphae into multigenomic compartments (276). In contrast, during sporulation-specific cell division in aerial hyphae, many septa are formed almost simultaneously and in a highly symmetrical fashion, followed by the formation of spore compartments and cell fission, resulting in chains of spores that each contain a single copy of the chromosome (reviewed in references 277 and 278).…”
Section: From Aerial Hyphae To Spores: Sporulation-specific Cell Divimentioning
confidence: 99%
“…To visualize the localization hierarchy of SsgB-eGFP and FtsZ-mCherry live during the initiation of sporulationspecific cell division, we further developed the technique of time-lapse imaging (Jyothikumar et al 2008) to image proteins in aerial hyphae. This unequivocally supported the fluorescence microscopy data, with SsgB localizing to cell division sites first, followed some minutes later by FtsZ ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, replication is asynchronous, and only selected chromosomes undergo replication at any given time (17). Recently, a new method for monitoring Streptomyces hyphal growth in real time using time-lapse microscopy was established by Jyothikumar et al (11). It showed that, following germination, hyphal extension occurred at about 20 m h Ϫ1 when grown on mannitol-supplemented minimal medium at 30°C.…”
mentioning
confidence: 99%